Associations of adiposity, circulating protein biomarkers, and risk of major vascular diseases - Pang, Y; Kartsonaki, C; Lv, J; Fairhurst-Hunter, Z; Millwood, IY; Yu, C; Guo, Y; Chen, Y; Bian, Z; Yang, L; Chen, J; Clarke, R; et al. (American Medical Association, 2020)
Importance Obesity is associated with a higher risk of cardiovascular disease (CVD), but little is known about the role that circulating protein biomarkers play in this association.